2009
DOI: 10.1108/01409170910927578
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture and performance: a Brazilian case

Abstract: PurposeThe purpose of this research project is to focus on the acquisition of a Brazilian state owned energy distribution company by a Spanish conglomerate during the privatization process. It aims to verify if the performance indicators implemented by the acquiring company during the post‐acquisition phase were compatible with the organizational culture (OC) dimensions identified by Hofstede et al. It tries to identify if the values and practices fostered by the company transformation plan (such as democratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To encourage an organization to improve its performance and maintain it continuously, it requires an organizational culture. In-depth studies have shown that organizational culture plays a role in improving employee performance (Ali Alsheikh, Abd Halim, Ahmad Alremawi, & Bin A Tambi, 2018;Biswas, 2009) and organizational performance (Alghamdi, 2018;de Hilal, Wetzel, & Ferreira, 2009;Dong-qin, Surname, & Surname, 2006;García-Fernández, Martelo-Landroguez, Vélez-Colon, & Cepeda-Carrión, 2018;Gorondutse & Hilman, 2018;Ibrahim, Mahmood, & Bakar, 2018;Lu & Li, 2008;Mallak et al, 2003;Ogbonna & Harris, 2000;Yesil & Kaya, 2013;Yu & Wang, 2018), developing flexibility (Weihong & Dan, 2008), effectivity (Deem, DeLotell, & Kelly, 2015;B. T. Gregory, Harris, Armenakis, & Shook, 2009;I.…”
Section: Introductionmentioning
confidence: 99%
“…To encourage an organization to improve its performance and maintain it continuously, it requires an organizational culture. In-depth studies have shown that organizational culture plays a role in improving employee performance (Ali Alsheikh, Abd Halim, Ahmad Alremawi, & Bin A Tambi, 2018;Biswas, 2009) and organizational performance (Alghamdi, 2018;de Hilal, Wetzel, & Ferreira, 2009;Dong-qin, Surname, & Surname, 2006;García-Fernández, Martelo-Landroguez, Vélez-Colon, & Cepeda-Carrión, 2018;Gorondutse & Hilman, 2018;Ibrahim, Mahmood, & Bakar, 2018;Lu & Li, 2008;Mallak et al, 2003;Ogbonna & Harris, 2000;Yesil & Kaya, 2013;Yu & Wang, 2018), developing flexibility (Weihong & Dan, 2008), effectivity (Deem, DeLotell, & Kelly, 2015;B. T. Gregory, Harris, Armenakis, & Shook, 2009;I.…”
Section: Introductionmentioning
confidence: 99%
“…Although organizations in the same industry or environment tend to engage the in same cultures of running a business (Oney-Yazici et al, 2007), innovative and non-innovative organizations can be differentiated by cultures that are present within the organizations Martin and Terblanche (2003). The way an organization operates its business, adapts to external pressure or deals with internal differences is determined by its culture (Hilal et al, 2009). In addition, pessimistic behaviors such as a refusal to accept change and withdrawal are also influenced by cultures (VargasHernandez and Noruzi, 2009;Yusof and Shafiei, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This system of shared values and beliefs interacts with the organizational structure, its members, and the control systems, producing norms of behavior ( Harrison, 1972 ). It can also be described as a set of meanings and values that, as building blocks, configure the culture and are expressed through symbols, behaviors, and organizational structures ( Garibaldi et al, 2009 ), allowing them to interpret such actions and judge them as appropriate or inappropriate. The evolution of a certain culture is attributed to an organizational learning process whether facing external or internal problems ( Schein, 1990 ).…”
Section: Theorymentioning
confidence: 99%